Clinicopathologic Features and Outcomes in Fibronectin Glomerulopathy: A Case Series of 19 Patients - Zhang, Ti; Zhang, Wei; Zuo, Ke; Cheng, Zhen (Frontiers in Medicine, 2020)
Abstract Aims: To describe the characteristics and prognosis of 19 patients with fibronectin glomerulopathy (FNG) and evaluate prognostic factors associated with poor renal outcomes. Methods: Included in this retrospective study was 19 FNG patients in Nanjing Glomerulonephritis Registry system. Associations between the clinical parameters, pathological features and renal outcomes were evaluated by Kaplan-Meier survival analysis. Results: Of the 19 FNG patients included in this study, 8 (42.1%) were women. The median age of the 19 FNG patients was 31 (17-71) years, and the median disease duration 48 (1–175) months at diagnosis. At the time of renal biopsy, the mean serum creatinine (Scr) was 1.22 ± 0.16mg/dl and urinary protein was 6.24± 0.97 mg/24 h. Renal biopsy showed a lobular appearance with cellular mesangial nodules expanded by matrix in 14 cases. After a median follow-up period of 87 months (interquartile range 34–114.5 months), 8 FNG patients developed renal function decline, including 7 progressing into end-stage renal disease (ESRD) and 1 presenting with by a 2-fold-increase in Scr. Scr and proteinuria remained stable in the remaining 11 patients. Kaplan-Meier survival analysis showed that nephrotic range proteinuria (P=0.022) and focal segmental glomerusclerosis (P=0.028) were associated with renal function decline (P=0.022 and P=0.028). Conclusions: Nephrotic range proteinuria and focal segmental glomerusclerosis were associated with renal function decline during the follow-up period of the FNG patients in our series. FNG Patients at risk of renal function decline should be identified preferentially and given more progressive and effective therapies to prevent further disease progression.